Clinical relevance of maximal inspiratory pressure: determination in COPD exacerbation - Voicu Tudorache; Cristian Oancea; Ovidiu Fira Mlădinescu (International Journal of COPD, 2010)
Voicu Tudorache1, Cristian Oancea1, Ovidiu Fira Mlădinescu21Department of Pneumology, 2Department of Pathophysiology, Victor Babeş University of Medicine and Pharmacy, Timişoara, RomaniaAbstract: Muscle dysfunction represents a pathophysiological feature of chronic obstructive pulmonary disease (COPD). Muscle impairment contributes to decreased effort capacity in these patients at least in the same proportion as pulmonary function limitation. Maximal inspiratory pressure (MIP) is a reliable, noninvasive parameter for assessing the respiratory muscle capacity. The aim of the present study was to determine the role of MIP in effort capacity decrease in COPD patients. MIP was measured in 121 COPD patients without hyperinflation (RV < 150%) together with the following investigations: body plethysmography, body impedance analysis, dynamometry, 6-minute walking test (6MWT), determination of SaO2 and serum levels of highly sensitive C-reactive protein (hsCRP). MIP (kPa) was significantly decreased in moderate-severe stages (6.19 ± 2.42, COPD II; 5.35 ± 2.49, COPD III; 4.56 ± 1.98, COPD IV vs 7.90 ± 2.61 in controls, P < 0.001), whereas the muscle force assessed by dynamometry was decreased only in advanced stages of disease (0.47 ± 0.12, COPD III; 0.41 ± 0.07, COPD IV vs 0.71 ± 0.16 in controls, P < 0.001). The values of MIP correlated (r = 0.53, P = 0.0003) with the distance walked in 6MWT. MIP may provide additive information concerning the general profile of muscle dysfunction in COPD patients.Keywords: COPD, MIP, exacerbation